Energy Harvesting of Ionic Polymer-Metal Composites Based on Microcellular Foamed Nafion in Aqueous Environment - Byung Chul Kweon; Joo Seong Sohn; Youngjae Ryu; Sung Woon Cha (Actuators, 2020)
The purpose of this study was to determine how to improve the energy-harvesting properties of polymer electrolyte membranes by varying their porosity. We achieved this by applying microcellular foaming process (MCP) to Nafion-based ionic polymer–metal composites (IPMCs). We manufactured an IPMC by forming a Pt electrode through an electroless plating method on the Nafion film, to which porosity was imparted by varying the foaming ratio and inducing deformation by vibrating the specimen using a prototype device that we developed ourselves. We attempted to harvest energy via fluid flow that occurred owing to displacement movement. When the Nafion film was foamed at a temperature of 140 °C or higher, it was observed that cells with size of approximately 1 µm or more were formed, and when the saturation temperature was lowered, a denser and larger number of cells were formed. Moreover, the cells formed on the electrolyte membrane allowed the retention of more water. Water retention generated charges contributed to the operational stability of IPMC. This was attributed to the difference in the amount of charge generated by changing only the internal morphology of the electrolyte membrane, without changing the substrate or the electrode material.